KOMUNIKASI BUDAYA DALAM TRADISI NGELOWONG MASYARAKAT SASAK WETU TELU DI LOMBOK - I Wayan Sudiartawan; I Wayan Sutama (IAHN Gde Pudja Mataram, 2022)
The Sasak Wetu telu indigenous people are a society that still maintains traditions in an effort to preserve and harmonize natural ecosystems. This tradition is still being carried out even though it is increasingly minimal. The purpose of this article is to describe cultural communication in the ngelowong tradition in the Sasak Wetu Telu indigenous people. The research approach uses descriptive qualitative with field research. Data collection is done by observation, documentation, and interviews. The results of the study show that cultural communication in ngelowong by the Sasak indigenous people is an expression to maintain existence, to maintain harmony with nature. Ngelowong is carried out by using natural means as an effort to ward off disturbances or pests to the plants in the fields.